Experience and coping strategies of parents of children with autism: A qualitative study - Archana Bagale; Anil Raj Ojha; Machhindra Lamichhane (PLoS ONE, 2025)
Background The neurodevelopmental disorder known as autism spectrum disorder (ASD) affects people of all racial, ethnic, and socioeconomic backgrounds. Although the study of autism is burgeoning with important implications both for public health and society, there is little research exploring the experiences of raising a child with autism spectrum disorder (ASD) from the Parent’s perspectives. The aim of this study was to explore experiences and coping strategies of parents of children with ASD in Nepal. Methodology A descriptive phenomenological design explored the lived experiences of nine parents raising children with ASD in Nepal. Participants were purposively selected from the Pediatric OPD of Patan Academy of Health Sciences. Data were collected through in-depth, semi-structured interviews in Nepali and analyzed using Colaizzi’s method. The interview guide, adapted from Batchelor (2017) and the Chronic Sorrow Instrument, explored emotional, social, financial, and caregiving experiences. Researcher bias was minimized through bracketing and reflexive journaling, and trustworthiness ensured via member checking, audit trails, and peer debriefing. Ethical approval was obtained from the PAHS Ethical Review Board, with informed consent and confidentiality maintained. Results Five major themes emerged: psychological impact (emotional burden, hope and uncertainty, guilt), physical impact (fatigue, sleep deprivation, safety concerns), social impact (isolation, stigma, family sacrifices), career impact (job loss, reduced opportunities), and financial impact (high costs, limited resources). Coping strategies included crying, listening to religious music (bhajans), meditation, and practicing positive thinking. Some parents reframed their experience as an opportunity to help others. Conclusion Parents raising children with autism in Nepal face profound emotional strain, physical fatigue, social isolation, career disruption, and financial pressure. These challenges were especially evident among mothers, who formed the majority of caregivers. Despite early diagnosis and continued care, families reported limited resources and persistent social stigma. Yet, many parents showed determination and resilience in supporting their children’s development. These findings emphasize the need to strengthen family-centered support, accessible services, and community awareness to better address the lived realities of caregivers.